FACTORS AFFECTING THE PERCEPTION OF SATISFACTION OF ANGKUTAN KOTA USERS - Wita Meutia; Prima Jiwa Osly; Mochamad Farhan Rahmat Saputra (Jurnal Infrastruktur, 2023)
One of the means of land transportation that is still used by some people to assist mobility in their activities is city transportation. Urban transportation or also known as angkot is a form of transportation that is familiar to most Indonesian people. City Transportation D.02 is one of the prima donna of urban transportation in Depok City. The purpose of this study is 2. To analyze the factors that influence the community to continue to use City Transportation route D.02. In this final project research was conducted by distributing questionnaires to users of City Transportation D.02 route Terminal Depok - Depok II Tengah in several places. The questionnaire contains the factors that influence people to use public transportation. In the correlation analysis with Y1 is the variable How satisfied are you with the service of Angkot D.02 there are only 8 variables out of 22 correlated independent variables (X). The highest Pearson Correlation value is 0.462 on the variable I feel that my travel time is in accordance with the distance traveled. And with Y2 is the variable How much do you agree to travel using Angkot D.02 even though you have a private vehicle there are 18 variables out of 22 correlated independent variables (X). The highest Pearson Correlation value is 0.597 in the Angkot interior condition variable D.02 which is quite interesting. In the factor analysis with the Component Extraction and Varimax Rotation test, seven factors were formed.